Gallium citrate-67 single-photon emission computed tomography/computed tomography for localizing the foci of classic fever and inflammation of unknown origin: A retrospective study of diagnostic yield - Seiichiro Tsuzuki; Ayumi Watanabe; Mitsunaga Iwata; Hiroshi Toyama; Teruhiko Terasawa (Asia Oceania Journal of Nuclear Medicine and Biology, 2021)
Objective(s): Only few studies have assessed the use of gallium citrate-67 single-photon emission computed tomography/computed tomography (67Ga-SPECT/CT) for localizing the foci of classic fever of unknown origin (FUO) and inflammation of unknown origin (IUO). Hence, the current study aimed to assess the diagnostic contribution of 67Ga-SPECT/CT in a tertiary referral setting where nuclear imaging tests are performed after an unsuccessful comprehensive primary diagnostic workup.Methods: We retrospectively assessed the medical records of 27 adult patients with FUO/IUO who had an unsuccessful diagnostic workup and who underwent 67Ga-SPECT/CT for the localization of FUO/IUO foci in our university hospital between 2013 and 2019. The primary outcome was diagnostic yield. The secondary outcomes were overall clinical efficacy and spontaneous remission of FUO/IUO symptoms in patients with a negative 67Ga-SPECT/CT finding.Results: Almost all patients completed the recommended diagnostic workup, except for urine culture and abdominal ultrasonography. Moreover, prior to 67Ga-SPECT/CT, all patients underwent thoraco-abdominopelvic CT scan, which was a non-diagnostic procedure. After a median follow-up of 843 days, the cause was identified in 16 (59%) patients. 67Ga-SPECT/CT successfully localized the FUO/IUO foci in eight patients (diagnostic yield = 30%; 95% confidence interval [CI]: 14%–50%). However, the causes remained unknown during follow-up in 11 (41%) patients. Among them, five experienced spontaneous regression of symptoms. 67Ga-SPECT/CT was negative in four of the five patients with spontaneous regression in symptoms without a definite cause. Considering this an important event, the overall clinical efficacy of 67Ga-SPECT/CT increased to 44% (95% CI: 25%–65%).Conclusion: 67Ga-SPECT/CT had an acceptable diagnostic yield for the localization of FUO/IUO foci, which are challenging to diagnose, in a contemporary tertiary referral care setting. In patients who experienced spontaneous regression in symptoms with an unexplained cause, the absence of abnormal uptake might indicate prospective spontaneous remission. Thus, 67Ga-SPECT/CT could be an active first-line nuclear imaging modality in settings where fluorine-18-fluorodeoxy glucose positron emission tomography and computed tomography is not available for the assessment of FUO/IUO causes.